Developmental Biology Protocols : Volume III - Tuan, Rocky S. (Totowa, NJ : Humana Press Inc., 2000., 2017)
The molecular biology revolution has transformed developmental biology into one of the most exciting and fruitful fields in experimental biomedical research today. In Developmental Biology Protocols, established leaders in this field demonstrate this achievement with a comprehensive collection of cutting-edge protocols for studying and analyzing the events of embryonic development. Drawing on state-of-the-art cellular and molecular techniques, as well as new and sophisticated imaging and information technologies, this 3rd volume and last volume introduces powerful techniques for the manipulation of developmental gene expression and function, the analysis of gene expression, the characterization of tissue morphogenesis and development, the in vitro study of differentiation and development, and the genetic analysis of developmental models of diseases. The 1st and 2nd volumes in this seminal set complete today's widest-ranging collection of techniques designed to decipher the exact cellular, molecular, and genetic mechanisms that control the form, structure, and function of the developing embryo. Volume 1 presents readily reproducible methods for establishing and characterizing several widely used experimental model systems, for both the study of developmental patterns and morphogenesis, and the examination of embryo structure and function. In addition, there are step-by-step methods for the analysis of cell lineage, the production and use of chimeras, and the experimental molecular manipulation of embryos, including the application of viral vectors. No less innovative, volume 2 describes state-of-the-art methods for the study of organogenesis, the analysis of abnormal development and teratology, the screening and mapping of novel genes and mutations, and the application of transgenesis, including the production of transgenic animals and gene knockouts. Highly practical and richly annotated, the three volumes of Developmental Biology Protocols describe multiple experimental systems and details techniques adopted from the broadest array of biomedical disciplines. Every researcher will not only better understand the principles, background, and rationale for how form and function are elaborated in an organism, but also gain full practical access to today's best methods for its analysis.